Inhibition of HLA-DM Mediated MHC Class II Peptide Loading by HLA-DO Promotes Self Tolerance - Denzin, Lisa K. (Frontiers in Immunology, 2013)
Major histocompatibility class II (MHCII) molecules are loaded with peptides derived from foreign and self-proteins within the endosomes and lysosomes of antigen presenting cells (APCs). This process is mediated by interaction of MHCII with the conserved, nonpolymorphic MHCII-like molecule HLA-DM (DM). DM activity is directly opposed by HLA-DO (DO), another conserved, non-polymorphic MHCII like molecule. DO is an MHCII substrate mimic. Binding of DO to DM prevents MHCII from binding to DM, thereby inhibiting peptide loading. Inhibition of DM function enables low stability MHC complexes to survive and populate the surface of APCS. As a consequence, DO promotes the display of a broader pool of low abundance self-peptides. Broadening the peptide repertoire theoretically reduces the likelihood of inadvertently acquiring a density of self-ligands that is sufficient to activate self-reactive T cells. One function of DO, therefore, is to promote T cell tolerance by shaping the visible image of self. Recent data also shows that DO influences the adaptive immune response by controlling B cell entry into the germinal center reaction. This review explores the data supporting these concepts.